Factors influencing the adoption of e-government by female university students - Paula Andrea Rodríguez-Correa; Carlos Alberto Méndez-Rivera; Orfa Nidia Patiño-Toro; Alejandro Valencia-Arias; Ada Lucia Gallegos Ruiz Conejo; Aarón Oré León; Jorge Tomás Cumpa Vásquez; Toño Eldrin Alvites Adan (PLoS ONE, 2025)
The primary purpose of electronic government (e-government) is to promote transparency, facilitate access to government services, and strengthen the accountability of public institutions in the digital transformation age. However, few studies have explored the factors that affect women’s adoption of e-government, especially in emerging economies. Consequently, this study aims to identify the factors that influence the adoption of e-government services by young women in Medellín, Colombia. To achieve this objective, a questionnaire was administered to a sample of 223 women, focusing on the factors proposed in the Technology Acceptance Model (TAM). The results were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings confirmed the validity of both the measurement and structural models, providing evidence for their predictive power. In addition, seven out of the eight hypotheses were confirmed, particularly highlighting the positive influence of ease of use on perceived usefulness, as well as the positive relationship between intention to use and actual use of the system. The results underscore the importance of reaching a more equitable and empowering participation of women in the digital government sphere. Moreover, they provide valuable insights for formulating policies and strategies that promote the effective adoption of e-government services by the demographic group under study.